The Landslide Distribution in Loano Sub-District, Purworejo District, Central Java Province, Indonesia - Sartohadi, Junun (Forum Geografi, 2008)
This research was proposed to figure out the importance of human influence on landslide disaster. The research objectives were: (1) to map the locations of landslide during the period of January 2004-March 2008 of the study area; (2) to map the degree of landslide hazard of the study area; (3) to analyze the distribution of landslide based on the landslide hazard map; and (4) to analyze the distribution of landslide based on the road network. The method of this research consists of field survey and laboratory works. The field survey was intended to map the location of landslide which happened during the period of January 2004 up to March 2008. The land characteristics and land qualities data have been collected based on geomorphological approach. The laboratory works were proposed to analyze the field data of land characteristics and land qualities for landslide hazards classification and mapping purposes. Scoring method was applied for landslide hazard evaluation. Some geographical information techniques were applied for mapping purposes and spatial data analysis of landslide distribution. Map overlay and buffering techniques were applied during landslide distribution analysis. The results of the research showed that: (1) there were 291 landslides collected during the research period; (2) the study area consists of very high, high, moderate, and low of landslide hazard classes. There was no safe area of landslide hazard within the study area; (3) most the landslide occasions were more influenced by human activities than derived by physical conditions. Some of human activities that induced landslide in the study area were slope cutting for: road construction, houses, agricultural purposes, and sand and stone mining in the river canal; (4) the spatial distribution of most landslide (>90%) were parallel with road networks.